DISTÚRBIOS OSTEOMUSCULARES RELACIONADOS AO TRABALHO: SITUAÇÃO NA CONSTRUÇÃO CIVIL EM GOIÂNIA - Débora Pereira Rosa, Débora Benchimol Ferreira; Maria Márcia Bachion (Universidade Federal de Goias, 2000)
Skeletal muscle disturbs related to the work: situation in the civil construction in Goiânia - The related muscle skeletal disturbs (WRMD), known as Repetitive Effort Lesion are world wide phenomenon, bringing negative repercussion to the workers, undertaking and the society. There are worker's categories considered at risk. This exploratory research sought to identify de display of WRMD and their repercussion among civil construction's workers in Goiânia, as well to identify the performance of nurses in the area of the civil construction relative the WRMD prevention. After explain consent announce, 105 workers, arising from public undertaking, private and autonomous. From 47 person that described pain in the characteristic regions of WRMD, 38 point pain in the first, 29 in the hand's fingers, 23 in the scapula's region and 16 in the shoulders, that don't motivated the search of the health services, removal or work accidents. We didn't find relate of the use direction about WRMD prevention. It doesn't appear in the individual's account the nurse's of the work figure. We concluded that the WRMD manifestations haven't great repercussion on the workers yet, because it is an area that doesn't have the nurse performance yet.